2016
DOI: 10.1016/s0140-6736(16)00087-8
|View full text |Cite|
|
Sign up to set email alerts
|

Renal apnoea: extreme disturbance of homoeostasis in a child with Bartter syndrome type IV

Abstract: Word count: 960

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
(4 reference statements)
1
14
0
Order By: Relevance
“…Several dated human and animal studies have shown compensatory hypoventilation in metabolic alkalosis 12,13,28‐30 . This in line with more recent reports of infants with apnea caused by severe metabolic alkalosis due to (pseudo‐) Bartter syndrome, peritoneal dialysis with bicarbonate containing solutions, and consumption of gripe water, containing an high concentration of sodium bicarbonate by a previously healthy infant 31‐34 . In infants with postoperative apnea, it was unclear whether the infants presented with metabolic alkalosis or not and whether this may have led to postoperative apnea 22,23 .…”
Section: Discussionsupporting
confidence: 54%
“…Several dated human and animal studies have shown compensatory hypoventilation in metabolic alkalosis 12,13,28‐30 . This in line with more recent reports of infants with apnea caused by severe metabolic alkalosis due to (pseudo‐) Bartter syndrome, peritoneal dialysis with bicarbonate containing solutions, and consumption of gripe water, containing an high concentration of sodium bicarbonate by a previously healthy infant 31‐34 . In infants with postoperative apnea, it was unclear whether the infants presented with metabolic alkalosis or not and whether this may have led to postoperative apnea 22,23 .…”
Section: Discussionsupporting
confidence: 54%
“…The clinical consequences reflect the role of the affected transport protein: it can be isolated loss of specific solutes, which may even be of clinical benefit, considering, for instance, isolated renal glycosuria owing to mutations in the sodium-glucose cotransporter type 2. But they can also be devastating if global homeostasis is affected, impairing even the most basic physiologic functions, such as respiration (2).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the macula densa, the site of tubuloglomerular feedback (TGF) is part of the TAL. Thus, impaired salt reabsorption in TAL leads to a Bshort-circuiting^of TGF with increased renin production, which is irrespective of volume status [9][10][11].…”
Section: Salt Reabsorption In the Talmentioning
confidence: 99%